Factors associated with interest in scientific research in dental students of six Cuban universities - Corrales-Reyes, Ibraín Enrique (2023)
“Introduction: To determine the factors associated with interest in scientific research in dental students of six Cuban universities. Methods: This is a multicenter cross-sectional analytical study. Interest in scientific research was the dependent variable, and it was assessed through a questionnaire proved to be reliable (Cronbach’s α= 0.88). We obtained adjusted prevalence ratios (aPR), 95% confidence intervals (95% CI), and p values through generalized linear models. Results: A total of 587 students were part of the research, and 57.9% manifested interest in scientific research. However, when they were asked if they wanted to pursue a research career in the future, only 45.1% responded affirmatively. We found, through multivariate analysis, that there was more interest in scientific research among those who were student assistants (aPR: 2.42; 95% CI: 1.41–4.16; p = 0.001), those who had previous studies (aPR: 1.35; 95% CI: 1.02–1.79; p = 0.034), and those who had received awards in scientific events (aPR: 1.74; 95% CI: 1.26–2.41; p = 0.001). In contrast, there was less interest among those who were at the clinical stage of their career (aPR: 0.66; 95% CI: 0.49–0.89; p = 0.006), adjusted for seven variables. Conclusions: There exists interest in scientific research and we found some factors associated with this. This has to be taken into account in order for educational institutions to generate strategies.“